ANALYSIS OF THE CONTINUOUS PROFESSIONAL DEVELOPMENT (PKB) PROGRAM MANAGEMENT THROUGH TEACHER WORKING GROUPS (KKG) IN PUBLIC ELEMENTARY SCHOOLS IN BABAHROT DISTRICT - Tasrullah; Murniati AR; Khairuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The Continuous Professional Development (PKB) Program for teachers is a systematic process of activities that teachers undertake to examine, assess, or reflect on their teaching practices after conducting teaching and learning activities to improve their professional competence. The purpose of this study is to determine the management, implementation, and obstacles of the Continuous Professional Development (PKB) Program through Teacher Working Groups (KKG) in Public Elementary Schools in Babahrot District. The approach used in this study is a qualitative approach with descriptive research. The research subjects are 15 classroom teachers, consisting of 7 classroom teachers who are members of the Teacher Working Group (KKG) at the elementary school level in Babahrot District, Southwest Aceh Regency, 7 school principals, and 1 school supervisor. Data collection techniques used by the researcher are observation, interviews, and documentation studies. Based on the research results, it can be concluded that 1) The management of the Continuous Professional Development (PKB) Program through Teacher Working Groups (KKG) in Public Elementary Schools in Babahrot District has not been fully implemented. The planning and organization indicators are good, but the program accountability, which includes KKG activity reports, does not meet the criteria. The evaluation and follow-up indicators have been implemented well. 2) The implementation of the Continuous Professional Development (PKB) Program through Teacher Working Groups (KKG) in Public Elementary Schools in Babahrot District has not been fully optimal. The limited facilities and infrastructure, internet access, and skills in using technology hinder teacher participation in KKG activities. 3) The obstacles in implementing the PKB Program in Public Elementary Schools in Babahrot District are coordinating KKG schedules, limited funding or resources, difficulties in implementing KKG learning into the classroom, and limited internet access or technology skills.